(untitled) (Research, Society and Development, 2022)
Objective: This study aims to develop and validate the “OdontoUrgências-SUS” application for patients seeking emergency dental care from the public health system, which is going to indicate when signs and symptoms qualify as urgency, in addition to indicating the nearest places that the patient can be treated. Methodology: It refers to a methodological study based on systematic instructional design for patients through a cell phone application developed in three stages: application creation, software registration request and validation. Results: The present work presented as results the creation of an application, whose main function is to screen the user by filling in forms. Through the responses obtained, the platform redirects the user to the nearest health unit that meets their demand. To test the usability and satisfaction of the software, the validation and application of online forms was carried out for students and professors of dentistry, as well as for dental surgeons from the public network of Maceió. This validation showed high satisfaction and usability of the application. Conclusion: In this way, the application has great potential for innovation in clinical practice and helping the population.